Efficient GaAs nanowire solar cells with carrier selective contacts: FDTD and device analysis. (April 2022) - Prashant, D.V.; Agnihotri, Suneet Kumar; Samajdar, D.P.
Abstract: Nanowire (NW) solar cells (SCs) with III-V materials have demonstrated superior light harvesting and anti-reflection characteristics, while also consuming less material than planar SCs. However, the performance of NW-based SCs in actual applications falls short of expectations because to their high surface-to-volume ratio and short minority carrier lifetimes. To tackle this, core-shell radial junction SCs are proposed. However, it is extremely difficult to achieve precise doping in both core and shell of NWs while preserving defect-free interface characteristics in the experimental realization, resulting in poor p-n junction quality and significant recombination processes. In this article, we have proposed a core-shell heterojunction SCs composed of p-type GaAs NW as the core material and ITO/TiO2 as the shell material to achieve high efficiency. Using the finite-difference time-domain (FDTD) methodology, we have shown that a coating of ITO/TiO2 shell over a geometrically optimized GaAs core may considerably reduce the cell's optical losses. In addition, using Lumerical's Charge solver module we found that the use of n-type TiO2 coating as an electron-selective can significantly improve the minority carrier transport and collection in the device. The optimized structure has exhibited an efficiency of 18.43% even for low minority carrier life-time ( τ n ) of 100ps and carrier mobility ( μ n ) of 1000cm 2 V −1 s −1 while maintaining high surface recombination velocity (SRV) of 10 7  cm/s and 10 4  cm/s at contacts and TiO2 /GaAs interface, respectively.